A Comparison of English and Dutch Long-Stay Patients in Forensic Psychiatric Care - Senn, Dhanuja; Bulten, Erik; Tomlin, Jack; Völlm, Birgit (Frontiers in Psychiatry, 2020)
Background: A significant proportion of forensic patients in England are long-stayers. This can be problematic as individuals are kept in restrictive environments at potentially inappropriate levels of security for many years, sometimes decades. Improvements to the current English forensic mental health system to meet the needs of long-stay forensic patients more effectively might be informed by the Dutch service for long-stay forensic patients. Aims: To compare the characteristics of representative samples of long-stay patients in England and in the Netherlands in an attempt to draw conclusions on the degree to which the Dutch service model might be relevant to England Method: This cross-sectional study explores the relevance of the Dutch service model by comparing the characteristics of representative samples of long-stay patients in England (n=401) and the Netherlands (n=102). Descriptive statistics and analyses of differences between groups are presented. Results: Compared to their English counterparts, the long-stay Dutch patients were less likely to be diagnosed with schizophrenia, but more likely to have personality disorder and have committed sex offences. The English group were younger at first conviction and at first custodial sentence. The total number of offences and the proportion of violent offenders were similar, but the Dutch HCR-20 scores indicated a significantly higher risk of violence. Conclusions: Whilst there may be barriers to adopting the Dutch service model in England, the differences in the characteristics of the two groups studied here do not necessarily preclude this approach.